Zinc Supplementation Mitigates High Salt Diet-Induced Bone Damage: A Histological Evaluation of Osteocyte Apoptosis - Kaukab Anjum; Abdullah Qamar; Nomana Mahmood; Muhammad Marghoob Khan; Shazia Imran; Ayesha Ali (Journal of Rawalpindi Medical College)
Objective: This study aims to evaluate the protective role of zinc supplementation against bone damage induced by a high-salt diet, with a specific focus on osteocyte apoptosis in rats.